The influence of unsymmetrical power input to the core loss of single phase transformer - Nur Azidawati Abd Razak
This final year project describes about the influence of unsymmetrical AC power input to the core loss of a single phase transformer. The unsymmetrical ac voltage is generated using unidirectional (half wave) ac voltage controller circuit.